Nonlinear flow induced vibration for energy harvesting - Yohanes Wirawan Putranto (2014)
The recent development in vortex induced vibration (VIV) has led to new energy harvesting method which is done by exploring areas that have not been observed before. The VIV will produce a vortex shedding frequency in the structure which will be the main source of energy for the system. The focus of this report is to design a secondary generator which can fit the vortex induced vibration system. The secondary generator will function as a supplementary power source and also to increase the mass of system to produce the vibration with the required frequency. Different frequency applied to the system will produce different power generation and through the experiment, the optimum frequency to produce the maximum power generation has been discovered. Factors affecting the power generation has also been discussed further in this report. Not only those, the advantages and disadvantages of implementing the device to the system are also mentioned in the latter part of the report. By considering the power generated, producing factors and maintenance issues, it can be decided whether the secondary generator should be implemented to the whole system. Other than that, it should also be known whether the implementation of secondary generator is complementing the main generator or undermining the whole system.